2011
DOI: 10.1007/s00425-011-1562-1
|View full text |Cite
|
Sign up to set email alerts
|

Flower and early fruit development in a diploid strawberry, Fragaria vesca

Abstract: The diploid woodland strawberry, Fragaria vesca, is being recognized as a model for the more complex octoploid commercial strawberry, Fragaria × ananassa. F. vesca exhibits a short seed to seed cycle, can be easily transformed by Agrobacteria, and a draft genome sequence has been published. These features, together with its similar flower structure, potentially make F. vesca a good model for studying the flower development of other members of the Rosaceae family, which contains many economically important frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 42 publications
9
105
0
1
Order By: Relevance
“…Based on stringent criteria (Meyers et al, 2008), we identified 31 known and 38 novel miRNAs from F. vesca. Our identification and analyses of miRNAs in F. vesca benefited from the sequenced F. vesca genome (Shulaev et al, 2011), allowing accurate mapping of sequenced reads, a well-described developmental morphology of reproductive development (Hollender et al, 2012) that allowed accurate tissue and stage identification, and the availability of extensive transcriptome data sets in F. vesca Hollender et al, 2014), which enabled us to examine the expression patterns of miRNA precursors and miRNA target genes. Importantly, the established transformation protocol and the ease of gene knockout in a diploid background will enable future functional studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on stringent criteria (Meyers et al, 2008), we identified 31 known and 38 novel miRNAs from F. vesca. Our identification and analyses of miRNAs in F. vesca benefited from the sequenced F. vesca genome (Shulaev et al, 2011), allowing accurate mapping of sequenced reads, a well-described developmental morphology of reproductive development (Hollender et al, 2012) that allowed accurate tissue and stage identification, and the availability of extensive transcriptome data sets in F. vesca Hollender et al, 2014), which enabled us to examine the expression patterns of miRNA precursors and miRNA target genes. Importantly, the established transformation protocol and the ease of gene knockout in a diploid background will enable future functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…A seventh generation inbred line of Fragaria vesca, Yellow Wonder 5AF7 (Slovin et al, 2009), was grown in soil in growth chambers under 12 h of light as described previously (Hollender et al, 2012). Young unexpanded leaves of 6-month-old plants, unopened flowers between stages 8 and 12 (staging according to Hollender et al [2012]), open flowers (within 1 d of opening), and receptacles (10 DPA) were harvested with hand dissection to remove the achenes from each receptacle (Fig.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the essential tenets of the ABCE model for flower development are conserved in angiosperms, each family of flowering plants can exhibit different and sometimes unique characteristics. In Fragaria vesca, a diploid wild strawberry (also called woodland strawberry), flowers differ from those of Arabidopsis in several aspects (Hollender et al, 2012). The most striking distinction is the formation of several hundreds of independent carpels arranged in a spiral pattern on an enlarged stem tip, the receptacle.…”
mentioning
confidence: 99%
“…As part of developing F. vesca into a model plant for the Rosaceae family (Shulaev et al, 2011), we previously described in detail the morphological and developmental progression of F. vesca flower development (Hollender et al, 2012), dividing flower development from stage 1, floral primordial initiation, to stage 12, the completion of flower development. That work laid the foundation for this article in detailing transcriptomes of various floral tissues at different stages.…”
mentioning
confidence: 99%